1998
DOI: 10.1002/(sici)1097-4695(199812)37:4<659::aid-neu13>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Role for cell adhesion and glycosyl (HNK-1 and oligomannoside) recognition in the sharpening of the regenerating retinotectal projection in goldfish

Abstract: Cell‐adhesion molecules (CAMs) are thought to play crucial roles in development and plasticity in the nervous system. This study tested for a role for cell adhesion and in particular, the recognition of two glycosyl epitopes (HNK‐1 and oligomannoside) in the activity‐driven sharpening of the retinotopic map formed by the regenerating retinal fibers of goldfish. HNK‐1 is a prominent glycosyl epitope on many CAMs and extracellular matrix (ECM) molecules, including NCAM, L1, ependymin, and integrins, which have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…In agreement, the ablation of specific laminin chains alters SC proliferation, which in turn prevents the defasciculation and myelination of peripheral nerves (Colognato et al, 2005). In addition to integrins, laminins bind a variety of adhesive molecules that carry the L2/HNK1 carbohydrate adhesion recognition epitope (Schmidt and Schachner, 1998). PMP22 contains this epitope (Snipes et al, 1993); therefore, it may directly bind laminin.…”
Section: Discussionmentioning
confidence: 91%
“…In agreement, the ablation of specific laminin chains alters SC proliferation, which in turn prevents the defasciculation and myelination of peripheral nerves (Colognato et al, 2005). In addition to integrins, laminins bind a variety of adhesive molecules that carry the L2/HNK1 carbohydrate adhesion recognition epitope (Schmidt and Schachner, 1998). PMP22 contains this epitope (Snipes et al, 1993); therefore, it may directly bind laminin.…”
Section: Discussionmentioning
confidence: 91%
“…N-glysosylation sites are important for the proposed function of ependymin. They can serve as anchorage positions for different oligosaccharides such as glucuronic acid (Shashoua et al, 1986;Schmidt and Schachner, 1998). In addition, it has been suggested that residues of sialic acid attached to the Nglysosylation sites confer the ability to alter ependymin tertiary structure in the presence of calcium and allow its interaction with other ECM components (Ganss and Hoffmann, 1993;Hoffmann and Schwarz, 1996).…”
Section: Identification and Sequence Analysis Of The Epenhg Genementioning
confidence: 99%
“…Analysis of oligomannoses isolated from synaptosomes showed that the amount of the two major glycans containing five (man5) and eight(man8)mannosesincreasesduringdevelopmentwithman5being the predominant form in adult brain (Fu and Gurd, 1983). Oligomannoses also play a role in long-term potentiation of mouse hippocampal neurons (Lüthl et al, 1994) and in regeneration of retinotectal projections in goldfish (Schmidt and Schachner, 1998).…”
Section: Introductionmentioning
confidence: 99%